2007
DOI: 10.1002/fld.1482
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of inflow conditions for two‐ and three‐dimensional spatially developing mixing layers using large eddy simulation

Abstract: SUMMARYA series of spatially developing mixing layers are simulated using the large eddy simulation (LES) technique. A hyperbolic tangent function and data derived from boundary layer simulations are used to generate the inflow condition, and their effects on the flow are compared. The simulations are performed in both two and three dimensions. In two-dimensional simulations, both types of inflow conditions produce a layer that grows through successive pairings of Kelvin-Helmholtz (K-H) vortices, but the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Because the transition is itself dependent on the development of three-dimensional large-scale motions, this has necessarily required spatially evolving simulations in three dimensions. Comparative two-and three-dimensional simulations performed previously by the present authors (McMullan, Gao & Coats 2007 have confirmed that, without the three-dimensional large-scale motions, the flow does not undergo the type of transition seen in real mixing layers. It has also required realistic evolution of the inflected velocity profile through the progressive merging of the laminar boundary layers formed on the two sides of the splitter plate.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Because the transition is itself dependent on the development of three-dimensional large-scale motions, this has necessarily required spatially evolving simulations in three dimensions. Comparative two-and three-dimensional simulations performed previously by the present authors (McMullan, Gao & Coats 2007 have confirmed that, without the three-dimensional large-scale motions, the flow does not undergo the type of transition seen in real mixing layers. It has also required realistic evolution of the inflected velocity profile through the progressive merging of the laminar boundary layers formed on the two sides of the splitter plate.…”
Section: Introductionsupporting
confidence: 84%
“…If numerical simulations are performed in two dimensions no transition of the type that was seen in the experiments occurs and subharmonics of the fundamental Kelvin-Helmholtz mode continue to be excited naturally throughout the available flow length (McMullan et al 2007(McMullan et al , 2010. If the simulations are performed in three dimensions, on the other hand, the secondary streamwise vortices are able to develop and interact with the primary spanwise vortices to produce the transition at which point, as was shown in §4.3, there is a switch to the regime in which the large structures all undergo continuous linear growth.…”
Section: Dynamics Of Post-transition Mixing Layermentioning
confidence: 88%
See 1 more Smart Citation
“…The method applied here is very similar to that employed in previous studies of the idealised mixing layer by the author. 28,29 In those studies, it was found that the transition to turbulence, and the coherent structures in the turbulent flow were readily captured.…”
Section: A Laminar Inflow Simulation (Lis)mentioning
confidence: 99%
“…21,22 Whilst these simulations are attractive on grounds of computational cost, it has been shown that mixing layers confined to two-dimensional domains do not undergo the mixing transition, as the formation of the secondary instability is inhibited. 23,24 This has a knock-on effect on the growth of the mixing layer, and entrainment of fluid into it. 23 Furthermore, the specification of idealised inflow conditions with white noise disturbances, common in mixing layer simulations, 20,25 can lead to different types of streamwise vorticity being formed in the mixing layer when compared to highly two-dimensional white noise fluctuations, 26 or physically-correlated inflow disturbances.…”
mentioning
confidence: 99%